Resolving the status of the genera Gastrophysus and Geneion in the family Tetraodontidae (Teleostei: Tetraodontiformes) - Jelks, Howard L. (Zootaxa, 2018)
Maintaining a current list of valid names and taxonomy for biodiversity is an ever-increasing challenge for the Integrated Taxonomic Information System (ITIS 2017). Advances in molecular techniques and the discovery of many cryptic taxa have dramatically increased the number of species and resulted in revised interpretation of phylogenetic relationships. Occasionally it is necessary to resolve discrepancies in nomenclature to reflect current knowledge. Taxa that are harvested for consumption are particularly in need of name stability. In this paper evidence is presented for the use of the puffer genus Takifugu Abe 1949 over Gastrophysus Müller 1843 and Amblyrhynchote Bibron in Duméril 1855 over Geneion Bibron in Duméril 1855.